Pengaruh Audit Internal, Pengendalian Internal, Dan Komite Audit Terhadap Penerapan Good Corporate Governance(Study Empiris Pada Bumn Di Kota Surakarta) - Rhomand Cassandra, Febry, Dr. Triyono, SE, M.Si (2017)
One of the concepts that are currently become mainstream is the concept of good corporate governance (GCG). This concept is actually derived from the concept of good governance is more common, namely Good Governance. This is very important to how should the management of the implementation of good entity and how should the entity placed himself in the middle of the community, the nation and the state of the public accountability and etc. The purpose of this research is to obtain empirical evidence related to the influence of internal audit the internal pengedalian, and the audit committee in the implementation of Good Corporate Governance (GCG). The population in this research using the entire BUMN in Surakarta. Data analysis methods used in this research is to use quantitative data analysis methods. This research examines the hypothesis using multiple regression analysis method . The test result shows the internal audit and internal control is not a significant effect on good corporate governance BUMN in Surakarta, but the audit committee significant effect on good corporate governance BUMN in Surakarta.